Effect of GMAW on the Tensile Strength and Hardness of Commercial Steel - Suliman Elfallah, Saleh (International Journal of Computer Sciences and Engineering, 2022)
Gas metal arc welding (GMAW) is very popular welding processes in the industry. The welding parameters that has significance in demonstrating the welding quality such as welding current, welding voltage, Gas flow rate, wire feed speed, welding speed and wire size. Taguchi's design is considered an efficient and a powerful optimizing tool for better quality and higher output performance of manufacturing processes. In this study, GMAW has welded commercial steel under controlled parameters of base metal thickness, welding current and wire feed speed. The analysis using Taguchi's design made on the influence of welding parameters on the strength of the welding, the tensile strength and hardness. Higher tensile strength and hardness were obtained at higher base metal thickness, lower voltage and wire feed speed (WFS). The hardness increased with the increased internal stresses. Higher base metal thickness obtained higher effect on the higher tensile strength and hardness according to the noise conditions analysis and also higher tensile strength and hardness results followed by lower wire feed speed. The optimal process parameters favorable for strong and effective welding are base metal groove shape V, 20 V and 5.9 m/min WFS. These settings are recommended when welding commercial steel (EN 10025-2) using mild steel filler in GMAW